A polymerase ribozyme increases copying fidelity through pyrophosphate-mediated RNA repair - Alexandra D. Kent; Lucy L. Yang; Kyle H. Cole; Ivee A. Lee; Andrej Lupták (Proceedings of the National Academy of Sciences, 2026)
Prior to the emergence of the contemporary biosphere, the first replicating systems are thought to have progressed through an RNA-based stage. Such an evolving world would likely have transferred heritable information during replication using RNA polymerase ribozymes. Though substantial effort has been put forth toward evolving RNA polymerases, many variants suffer from premature termination and low fidelity, resulting in low yields of full-length or active sequences. Replication of longer sequences requires a sufficiently high fidelity to lend an evolutionary advantage to an evolvable system. Here, we demonstrate ribozyme-mediated repair of mismatched and damaged RNA sequences. Under conditions of saturating pyrophosphate concentrations, we show that a polymerase ribozyme can repair RNA sequences terminated in a mismatch to generate a triphosphorylated nucleoside, such as adenosine triphosphate, which we detect directly. Similarly, the ribozyme can remove a nucleotide with a nonextendable 2′-3′ cyclic phosphate or a nonextendable mismatch. This repair step increases the overall fidelity of RNA synthesis and allows polymerization along an extended template. The increased copying fidelity advances the long-standing goal of developing a self-replicating polymerase ribozyme.